MODEL PEMBELAJARAN PICTURE AND PICTURE DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS XI PADA MATA PELAJARAN SEJARAH MATERI KOLONIALISME DAN IMPERIALISME DI SMA JAUHARUL FALAH AL-ISLAMI TA. 2021/2022 - Amaliyah, Qonita Zikriyah; Yanto, Ferry (Universitas Batanghari Jambi, 2022)
This study which aims to improve learning is to determine student learning outcomes by applying the Picture and Picture method to history subjects in class XI at Pesantren Jauharul Falah Al-Islamy, Muaro Jambi Regency. This research was conducted in 2 (two) cycles, namely cycle I and cycle II. The results of this research have shown an increase in student learning outcomes in history subjects, especially on colonialism and imperialism in Indonesia after the implementation of learning using the Picture and Picture learning model. This is illustrated by the increase in the percentage and class average of each cycle. In the pre-cycle the average class was 56.4 with a percentage of 16% of students who completed, there was an increase although not significant in the first cycle with an average class of 62.9 with a percentage of 44% of students who completed, then in the second cycle there was an increase in learning outcomes. which is significant, namely with a class average of 86.8 with a percentage of 100% complete.